Urgensi Penerbitan Izin Jasa Penilai Properti Sederhana - Yudi Irwan; Dyah Sulistyani Ratna Sediati; Sugiyo Sugiyo (Jurnal USM Law Review)
The purpose of this research is to investigate the implementation of issuing permits for simple property appraisal services in Indonesia, the challenges in their issuance, and efforts to overcome them. The research method used is normative juridical research with a legislative approach. The urgency of this research lies in examining the implementation of issuing permits for simple property appraisal services in Indonesia. This study will elaborate on the results of the analysis of the implementation of permits for simple property appraisal services in Indonesia, associated with theories and regulations related to the issues under discussion. The results of this research indicate the issuance of permits for simple property appraisal services in Indonesia. It begins with prospective simple property appraisers going through the stages of becoming public appraisers, starting from basic education to the submission of a public appraiser permit. Constraints in the licensing process for simple appraisers often arise in the application submission phase and the applicants' lack of understanding in using the online application elSa-PK. This is due to the insufficient socialization of the application usage process with prospective appraisers.